(untitled) (diségno, 2020)
The research, presented here in summary form, investigates the contributions of architectural drawing in children’s books and literature. The role of drawing in aesthetic education, in education for the understanding of space and in the introduction of young readers to the world of 20th century architecture is of primary importance and the research aims to underline as case studies are only simple examples for readers who are cognitively less trained than adults, but describe a precise educational strategy that cannot be derogated from other means. The historical-critical investigation has its scope of observation the strict contemporaneity and aims to organize taxonomically the works collected and observed, proposing a textual analysis (in a graphic sense) of categories identified through the description and exegesis of some emblematic cases.